Hop - Hill, Tim (Universal Pictures, 2011)
E.B., the Easter Bunny's teenage son, heads to Hollywood, determined to become a drummer in a rock 'n' roll band. In LA, he's taken in by Fred after the out-of-work slacker hits E.B. with his car.
3-6.
K-3.
Language : Turkish, English, German.
Subtitle : Turkish, English, German.
Keywords: Movie -- animated films; Movie -- Kids/Family.; Squirrel -- Movie